3D Interconnected Honeycomb-Like Multifunctional Catalyst for Zn–Air Batteries - Jin, Tianxu; Nie, Junli; Dong, Mei; Chen, Binling; Nie, Jun; Ma, Guiping (Nano-Micro Letters, 2022)
Developing high-performance and low-cost electrocatalysts is key to achieve the clean-energy target. Herein, a dual regulation method is proposed to prepare a 3D honeycomb-like carbon-based catalyst with stable Fe/Co co-dopants. Fe atoms are highly dispersed and fixed to the polymer microsphere, followed by a high-temperature decomposition, for the generation of carbon-based catalyst with a honeycomb-like structure. The as-prepared catalyst contains a large number of Fe/Co nanoparticles (Fe/Co NPs), providing the excellent catalytic activity and durability in oxygen reduction reaction, oxygen evolution reaction and hydrogen evolution reaction. The Zn-air battery assembled by the as-prepared catalyst as air cathode shows a good charge and discharge capacity, and it exhibits an ultra-long service life by maintaining a stable charge and discharge platform for a 311-h cycle. Further X-ray absorption fine structure characterization and density functional theory calculation confirms that the Fe doping optimizes the intermediate adsorption process and electron transfer of Co. Highlights: 1 The unique initiator doping strategy is adopted to achieve high dispersion of Fe atoms in the catalyst. 2 The 3D interconnected structure manufactured by morphology control exhibited excellent electrocatalytic performance in speeding up the electrolytes streaming and electron transfer. 3 The Zn-air battery assembled with catalyst Fe8Co0.2-NC-800 could maintain a stable charge discharge platform in 1701 cycles of 311 h.